Acoustic examination of epoxy-glass insulator material - Ranachowski, P.; Ranachowski, Z.; Rejmund, F.; Stankiewicz , J. (Archives of Acoustics, 2005)
Ultrasonic, microscopic and acoustic emission (AE) methods were applied to investigate the microstructure of composite rods, used as a carrying element of the medium voltage insulators. Such features of material structure as homogeneity level and the appearance of defects were discussed. The research was aimed at determining the influence of the technology of epoxy-glass fabrication on quality parameters of the insulator rods. The results of acoustic testing were compared with the effects of microscopic investigation. Key words: composite insulator, epoxy-glass material, nondestructive ultrasonic measurements, acoustic emission.